Efektivitas Pelatihan Empathy Care Untuk Meningkatkan Empati Pada Mahasiswa Keperawatan - Tutut Gayanti; Sofa Amalia; Siti Maimunah (JIP (Jurnal Intervensi Psikologi), 2018)
Empathy has not been optimally applied to nursing service which may provide some disadvantages for the patient especially on patients such as nurses who are not friendly and indifferent to the complaints of patients. Learning about the empathy on the nurse can begin since becoming a nursing student. Therefore, need a effort to increase empathy one of them through the intervention of Empathy Care Training. Basically, Empathy care training is a sequence of activities in which the basic knowledge and the implementation of empathy are given. The aim of this study is to carry out the effectiveness of Empathy care training treatment so as to step-up the sense of empathy for nursing students. This paper is categorized as experimental research with non-randomized pretest-posttest design in which the 22 nursing students are divided into two groups, namely control and experimental groups. The result of this study shows that there are differences on the sense of empathy level between the control and experimental ones with level of significance p < 0,05 (p=0,000). Based on the result, it can be concluded that Empathy care training treatment effectively increase the sense of empathy for nursing students.Keywords: Empathy care training, Empathy, Nursing students